Italian influences in Andrés Bello (Iter, 2022)
In this detailed and highly documentedessay Bartolucci shows how important Italian influence was for AndrésBelli in its most deverse aspects. The chapter ofunpublished workf whichhas beenfavored here, pours over linguistic influence, being languageone o f Bello's favorite topics and for which he had a special sensitivity.The richness ofthe body o f notes shows how eagerly and accurately theauthor worked on the enormous amount ofnews relevant to the plot.